Comparison of Intravitreal Dexamethasone Implant and Ranibizumab in Vitrectomized Eyes with Diabetic Macular Edema - Jia-Kang Wang; Tzu-Lun Huang; Pei-Yao Chang; Wei-Ting Ho; Yung-Ray Hsu; Fang-Ting Chen; Yun-Ju Chen (Journal of Ophthalmology)
Purpose. This retrospective study aimed to compare the efficacy of intravitreal ranibizumab (IVR) and intravitreal dexamethasone implant (IDI) for pseudophakic vitrectomized eyes with diabetic macular edema (DME) in a single institution. Methods. Pseudophakic vitrectomized eyes with treatment-naïve center-involved DME were enrolled, with one eye in each patient. They were divided into two groups: one group receiving IDI every 3 to 4 months and another group receiving IVR using 3 monthly plus treat-and-extend injections, all with monthly follow-up for 6 months. Switch of intravitreal drugs or deferred macular laser was not allowed. Primary outcome measures included change in central foveal thickness (CFT) in 1 mm by spectral-domain optical coherence tomography and best-corrected visual acuity (BCVA) at Month 6. Results. Twenty-two eyes were included in the IDI group and 26 eyes in the IVR group. The baseline demographics, glycosylated hemoglobin level, intraocular pressure (IOP), BCVA, and CFT did not significantly differ (p>0.05). Compared to baseline data, CFT decreased and BCVA improved significantly after either IDI or IVR at Month 6 (p<0.05). Significantly better mean final BCVA (0.38 logMAR vs. 0.62 logMAR, p=0.04), more mean visual gain (−0.30 logMAR vs. −0.15 logMAR, p=0.02), lower mean final CFT (310.9 μm vs. 384.2 μm, p=0.04), and larger mean CFT decrease (−150.0 μm vs. −60.1 μm, p=0.03) were found in the IDI group compared to those in the IVR group. A smaller mean treatment number (2.6 vs. 5.6, p<0.001) and higher rate of postinjection ocular hypertension requiring topical hypotensive agent therapy (27.3% vs. 0%, p=0.0002) were demonstrated in the IDI group than those in the IVR group. Conclusion. We concluded that IDI and IVR can both effectively treat vitrectomized eyes with DME. Dexamethasone implants had significantly better visual/anatomical improvement, smaller treatment number, and higher rate of elevated IOP after injection than IVR in pseudophakic vitrectomized eyes with DME in a 6-month period.